Peningkatan Kemampuan Analisa Root-Cause Staf Produksi PT E-T-A Indonesia Dalam Upaya Penurunan Kecacatan - Irawan, Steven; Bisono, Indriati (Jurnal Titra, 2014)
PT E-T-A Indonesia is a manufactur company that produce electricity component such as circuit breaker and switch. As a electricity component maker that trusted by well-known brand all over the world such as Mercedes-Benz, Audi, and also Airbus, quality is a must-have key in every single production activitiy. There are some defect problem that occurs in every production segment frequently. In order to reduce defect number, root-cause analysis skill is needed whereas most of production staff doesnât have enough skill to analyze the root-cause problem. The improvement of root-cause analysis skill is using DMAIC methods. Its begin with Define phase where all of the problem that happens are defined including quality characteristic of their products itself. The next phase is measure phase, the defect problem that happens in 1170 and 1180 from January until March 2014 are measured and counted into as a data in this phase. Analyze phase is a next-step phase where the main cause of the main problem are analyzed conscientiously, in this case, the main cause is founded, that is incapability skill of analyzing the root-cause of a problem in 1170 and 1180 worker. The next phase is improvement phase, the worker of 1170 and 1180 are trained with the right quality tools in order to make an root-cause analyze in case another problem happen. Evaluation of these improvement is monitoring the worker skill to do root-cause analyze correctly. Evaluation is a final phase that called control phase in this final project.